Pengaruh Kebudayaan, Sosial, Pribadi, dan Psikologi Terhadap Keputusan Konsumen dalam Penggunaan Grab Car pada Mahasiswa Fakultas Ilmu Sosial dan Politik Universitas Sam Ratulangi Manado - Maukeno, Angel V. A. P.; Taroreh, Henny S.; Punuindoong, Aneke Y. (Sam Ratulangi University, 2019)
The purpose of this research is to know the existence of factors influence a company's marketing, personal, social, cultural and psychological effects are significant for consumer behaviour in the use of Grab Car. Consumer behavior is a process undertaken by someone in finding, buying, using, evaluating, and disposing of a product or service after it is consumed, the study was conducted at the Faculty of social and political sciences of the University of Sam Ratulangi Manado by taking 100 students as the respondent. Withdrawal methods used is the sample Random Sampling with data analysis using multiple regression. By using the test validity and reliability in order to test the validity of the data. The results of this research show that cultural factors, social, personal, and psychology at the same time positively and significantly to the decision of the consumer in using the Grab Car with personal factors the most dominant, and it has high determination coefficient values, or have a great contribution towards the decisions of consumers.